18 INTEGRAREA ŞTIINŢEI ŞI ÎNVĂŢĂMÂNTULUI SUPERIOR ÎN CONTEXTUL PROCESULUI DE LA BOLOGNA - USM ADMIN (Moldova State University, 2007)
The article is dedicated to the problem of integration of science and higher education on the level of Bologna Process. There are reflected the tendencies on the European and national planes, the relation between teaching-studding- researching, is being discussed in higher education. Special attention is paid to doctoral education.